Single-Arm 8-Week Ad Libitum Self-Prepared Paleo Diet Reduces Cardiometabolic Disease Risk Factors in Overweight Adults. Issue 6 (November 2021) - Markofski, Melissa M.; Jennings, Kristofer; Dolan, Chad; Davies, Natalie A.; LaVoy, Emily C.; Ryan, Edward J.; Carrillo, Andres E.
The paleo diet is popular among the general population due to promoted weight loss and disease prevention benefits. We examined the effectiveness of a self-administered paleo diet in improving cardiometabolic disease risk factors. Overweight, physically inactive but otherwise healthy adults (males = 4, females = 3, age 32.7 ± 4.9 years, body mass index [BMI] 29.4 ± 2.4 kg/m 2 ) habitually eating a traditional Western diet (1853.4 ± 441.2 kcal; 34.0% carbohydrate; 41.4% fat; 19.2% protein) completed an ad libitum self-administered paleo diet for 8 weeks. Height, weight, blood pressure, and a fasting blood sample were collected pre– and post–paleo dietary intervention. Blood samples were analyzed for fasting cardiometabolic disease biomarkers—including brain-derived neurotropic factor (BDNF), fibroblast growth factor (FGF) 21, and leptin. After 8 weeks, body mass (−5.3 kg, P = .008), BMI (−1.7 kg/m 2, P = .002), serum leptin (−56.2%, P = .012), serum FGF21 (−26.7%, P = .002), and serum BDNF (−25.8%, P = .045) significantly decreased. Systolic and diastolic blood pressure were unchanged following the paleo dietary intervention ( P > .05). Average energy intake (−412.6 kcal, P = .016) significantly decreased with the paleo dietary intervention mostly due to a reduction in carbohydrate consumption (−69.2 g; P = .003). An 8-week self-administered paleo dietary intervention was effective in improving cardiometabolic disease risk factors in a healthy, physically inactive overweight adult population.